Sodium Octanoate Modulates the Innate Immune Response of Bovine Mammary Epithelial Cells through the TLR2/P38/JNK/ERK1/2 Pathway: Implications during Staphylococcus aureus Internalization - Alva-Murillo, Nayeli; Ochoa-Zarzosa, Alejandra; López-Meza, Joel E. (Frontiers in Cellular and Infection Microbiology, 2017)
Bovine mammary epithelial cells (bMECs) contribute to mammary gland defense against invading pathogens, such as Staphylococcus aureus (intracellular facultative), which is recognized by TLR2. In a previous report, we showed that sodium octanoate [NaO, a medium chain fatty acid (C8)] induces (0.25 mM) or inhibits (1 mM) S. aureus internalization into bMECs and differentially regulates the innate immune response (IIR). However, the molecular mechanisms have not been described, which was the aim of this study. The results showed that α5β1 integrin membrane abundance (MA) was increased in 0.25 mM NaO-treated cells, but TLR2 or CD36 MA was not modified. When these receptors were blocked individually, 0.25 mM NaO-increased S. aureus internalization was notably reduced. Interestingly, in this condition, the IIR of the bMECs was impaired because MAPK (p38, JNK, and ERK1/2) phosphorylation and the activation of transcription factors related to these pathways were decreased. In addition, the 1 mM NaO treatment induced TLR2 MA, but neither the integrin nor CD36 MA was modified. The reduction in S. aureus internalization induced by 1 mM NaO was increased further when TLR2 was blocked. In addition, the phosphorylation levels of the MAPKs increased, and 13 transcriptional factors related to the IIR were slightly activated (CBF, CDP, c-Myb, AP-1, Ets-1/Pea-3, FAST-1, GAS/ISRE, AP-2, NFAT-1, OCT-1, RAR/DR-5, RXR/DR-1, and Stat-3). Moreover, the 1 mM NaO treatment up-regulated gene expression of IL-8 and RANTES and secretion of IL-1β. Notably, when 1 mM NaO-treated bMECs were challenged with S. aureus, the gene expression of IL-8 and IL-10 increased, while IL-1β secretion was reduced. In conclusion, our results showed that α5β1 integrin, TLR2 and CD36 are involved in 0.25 mM NaO-increased S. aureus internalization in bMECs. In addition, 1 mM NaO activates bMECs via the TLR2 signaling pathways (p38, JNK, and ERK1/2), which improves IIR before S. aureus invasion. Additionally, NaO (1 mM) might exert anti-inflammatory effects after bacterial internalization.